2017
DOI: 10.15517/rbt.v65i3.29440
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution and microhabitat use of aquatic breeding amphibians (Anura) in a seasonally dry tropical forest in Chamela, Mexico

Abstract: Abstract:The distribution of amphibians is affected by abiotic and biotic factors, availability of resources and the characteristics of reproductive sites. In particular, reproductive activity of aquatic-breeding anurans that inhabit tropical dry areas is affected by rainfall, which determines the availability and quality of reproductive sites. In this study, we analyzed the spatial and temporal distribution of anurans with indirect development in a tropical dry forest in Western Mexico, during two rainy seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
6
0
4
Order By: Relevance
“…2014), and contraction of annual rainfall patterns could increase interspecific competition by changing the temporal segregation between breeding events (Luna‐Gomez et al. 2017). In areas subject to aridification under climate change, reductions in hydroperiod will increase the risk of recruitment failure due to pool desiccation (Chandler et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014), and contraction of annual rainfall patterns could increase interspecific competition by changing the temporal segregation between breeding events (Luna‐Gomez et al. 2017). In areas subject to aridification under climate change, reductions in hydroperiod will increase the risk of recruitment failure due to pool desiccation (Chandler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Changing rainfall volume and patterns are projected to affect amphibians at several points during their lifecycle. Changes in the seasonal onset of rainfall will likely affect the temporal initiation of breeding (Ludovisi et al 2014), and contraction of annual rainfall patterns could increase interspecific competition by changing the temporal segregation between breeding events (Luna-Gomez et al 2017). In areas subject to aridification under climate change, reductions in hydroperiod will increase the risk of recruitment failure due to pool desiccation (Chandler et al 2016), and increasing duration or severity of droughts will increase the frequency of recruitment failure (Dodd 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Both species reportedly adapt well to anthropogenic landscapes and are regularly found in close proximity to human settlements (e.g. Campbell 1998, Lee 1996, Leenders 2016, Lemos-Espinal & Dixon 2013, Luna-Gómez et al 2017, McCranie & Wilson 2002.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Santos et al (2008) We observed that the beginning and end of the breeding season of Dendropsophus sanborni coincide with the beginning and end of the rainy season, respectively (as defined by Koeppen; see Zaine and Perinotto, 1996). The seasonal distribution of anuran species activity can be influenced by several interrelated factors that are subject to daily, monthly, and annual variation (such as maximum and minimum temperatures, rainfall, and hydroperiod; e.g., Kopp and Eterovick, 2006;Hartel et al, 2007;Gally and Zina, 2013;Akmentins et al, 2015;Hurme, 2015;Luna-Gómez et al, 2017;Leivas et al, 2018). Thus, interactions of these factors may be responsible for variation in the reproductive periods of anurans.…”
Section: Seasonal Reproductive Activitymentioning
confidence: 99%
“…Among anurans, social organization is directly related to body size and reproductive traits such as chorus structure, male territoriality, pair formation, breeding site choice, and temporal breeding pattern (Wells, 1977;Martin et al, 2011;Rosa and Andreone, 2012;Sousa and Ávila, 2015;Berec, 2017). Moreover, temporal and spatial breeding patterns are affected by abiotic (e.g., climate and availability of reproductive resources) and biotic (e.g., habitat use, abundance of individuals, reproductive strategies, and adult life span) factors (Crump, 1974;Gally and Zina, 2013;Akmentins et al, 2015;Hurme, 2015;Luna-Gómez et al, 2017;Leivas et al, 2018). The majority of the anuran species from tropical areas with well-defined seasons possess seasonal reproductive dynamics associated with the hotter and rainier periods of the year (Shahriza et al, 2010;Van Sluys and Guido-Castro, 2011;Waldez et al, 2011;Schalk and Saenz, 2016).…”
Section: Introductionmentioning
confidence: 99%